CORRELATION BETWEEN RESPECT, RESPONSIBILITY, INTERPERSONAL RELATIONSHIP, SUPERVISION, AND COMPENSATION TO THE PERFORMANCE OF OFFICIAL RECORDER AT STATE HOSPITALS BUKITTINGGI WEST-SUMATRA INDONESIA - Alhamda, Syukra (BALI MEDICAL JOURNAL, 2013)
Objective: Primary survey was conducted on November 10, 2012 at The State Hospitals Bukittinggi, with randomly selected of 100 hospital medical records. There were incomplete contents of 61.66% and 48.33% of late files. This issue is very disturbing process for management of recording medical data. Therefore, it will disrupting functions of medical recorders. Method: This study applied cross-sectional study to determine the correlation between respect, responsibility, interpersonal relations, supervision and compensation for the performance of official recorders at The State Hospitals Bukittinggi West-Sumatra Indonesia. Questionnaires from the subjects were proceed and computed by applying chi-square test. Results: The results showed that there were significant correlation between the performance of official award recorders (p = 0.003 and OR = 9.208), responsibilities (p = 0.012 and OR = 6.094), interpersonal (p = 0.0025 and OR = 5.417), performance of official (p = 0.012 and OR = 6.094), and compensation of official recorders (p = 0.025 and OR = 5.417) to recorders performance. Conclusion: In this research, we observed that there was a significant correlation between respect, responsibility, interpersonal relations, supervision and compensation to the performance of official recorders. A greater attention should be considered in order to produce a good performance of the medical recorder.